An evaluation of the postgraduate diploma in Enterprise Management at Rhodes University - Earle, Nicola Lynne (Rhodes University, Faculty of Commerce, Department of Management, 2012)
This research is concerned with the development of entrepreneurship at higher education institutions (HEI). Entrepreneurship is very important in every country as there is a direct correlation between entrepreneurship development and economic growth (Hegarty, 2006). Entrepreneurship education is essential as it assists students who want to start up their own businesses by giving them the relevant skills and knowledge to have a successful business. The purpose of this research is to evaluate the Postgraduate Diploma in Enterprise Management (PDEM) within the Management Department at Rhodes University, Grahamstown. A qualitative approach was implemented which used an adapted version of the Context, Input, Process and Product Model (Stuffelbean, Mckee and Mckee, 2003). Data was collected in the form of interviews and focus group interviews. There were six lecturer interviews, one course coordinator interview and five past student interviews. There were two focus group interviews that took place; this was done so to gather data from seven current PDEM students. The data collected was then analysed through the use of qualitative data analysis techniques. These were sensing themes, constant comparison, recursiveness, inductive and deductive thinking and interpretation to generate meaning (Ruona 2005, cited in Swanson and Holton, 2005). The Management Department aims to equip students to think realistically in terms of starting their own business and to enhance the students' knowledge and skills so that they are better able to find employment in the corporate and government sectors. The PDEM aims to be an action-learning course and to create an entrepreneurial environment which will encourage students to start up their own businesses. The role of the lecturers and the course coordinator is important as they need to ensure that there is a continuous transfer of knowledge to the students. Students are not expected to be specialists within each subject; however they need to have a basic grounding in order to run a business. Students felt that the Alpha Project was important and useful as it improved their confidence about starting a new business. An issue that was raised about the Alpha Project was that the separation of students into the Alpha Project groups was not executed well. The course was perceived to be disorganised however the students tended to enjoy it and felt that the Management Department was supportive of their businesses.
Keywords: Rhodes University -- Curricula; Education, Higher -- Curricula -- South Africa -- Evaluation; Business education -- Curricula -- South Africa -- Evaluation; Business education -- Study and teaching -- South Africa